Financial Feasibility Study of PT Jasa Medivest Refinancing Plan - Muhammad, Ikhsan Armand; Surya, Budhi Arta (Journal of Business and Management, 2012)
Toxic Waste is always related in every single human activities, it will never separated from the human activities because toxic waste itself produce through the activities. For most of people, the main problem is in our country, most of the business empire did not have proper toxic waste management system that cause pollution. One of the toxic waste that happens to make some problem in the world is Medical waste, this type of waste is produce from every medical activity, it can happens from a giant hospital or Â private practice at home as long as there are a medical activity the happen in the area.Â  PT. Java Medivest is one of pioneer in medical waste management business sector, it began to operate since March 2009, with operating one unit of incinerator that have a capacity of 12 ton/day. PT. Jasa Medivest established by Foreigners Capital, with 95% of the shares is held by Pantai edivest Sdn.Bhd, Malaysia and the other 5% is for PT. Jasa Sarana. Incinerator PT. Java Medivest is in Interchange Road Toll Dawuan, Dawuan Tengah, Karawang, Jawa Barat.Purpose: The objective of this research is to determine whether the Refinancing fo PT. Java Medivest is feasible or not.Design/methodology/approach: The data will be process and analyze by concluding the problem solving model based on the method of making a good feasibility study, this model is a common type of model of concluding feasibility study.Findings: Equity capital according to the Deed Decree of Shareholder No. 25 dated November 8, 2011 made before Mala Mukti, SH, LL, M, Notary in Jakarta, with the amount of Rp.448.291.000.000, 00, divided into 48.1 million shares, each share par value is Rp.9.320, 00 . The changes, issued and paid-up capital has received approval from the Investment Coordinating Board according to his letter No. 2742/A.8/2011 dated October 31, 2011. From the capital, have been issued and paid up for 25.04% or 12,043,369 shares with a total nominal value of Rp.112.244.199.080, 00 by the shareholdersWith the proposed sale of all the shares owned by Pantai Medivest Sdn Bhd, Malaysia, the PT. Jasa Sarana is the sole shareholder. But according to the provisions Act of Limited Liability Company No. 40 of 2007, later than 6 (six) months after becoming the sole owner, PT. Jasa Sarana must release ownership of shares to investors. However PT Jasa Sarana committed will remain the majority shareholderOriginality/value: As a conclusion, the NPV of this project is Rp.2.728.182.294 and the IRR is 24,47%Keywords: Feasibility-Study; NPV; IRR; Payback-Period; Refinancing, Medical WasteCategory: Finance